2019
DOI: 10.9779/pauefd.486641
|View full text |Cite
|
Sign up to set email alerts
|

Üstün Yetenekli Öğrencilerin Değerler Eğitiminde Yaratıcı Drama Yönteminin Kullanılması: Adalet Değeri Örneği

Abstract: Bu araştırma üstün yetenekli öğrencilere verilecek değerler eğitiminde yaratıcı drama yönteminin sınanması amacıyla yapılmıştır. Araştırmanın çalışma grubunu Doğu Karadeniz Bölgesinde bulunan bir bilim ve sanat merkezinde destek eğitimi alan 3.sınıf seviyesindeki 8 öğrenci oluşturmaktadır. Araştırma üstün yetenekli öğrencilere 5 hafta süreyle toplamda 10 ders saatinden oluşan yaratıcı drama ile yapılandırılmış adalet eğitimi uygulamaları ile sınırlandırılmıştır. Uygulama öncesi ve sonrasında öğrencilerde adale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In this context, many studies have been conducted to determine the perceptions and attitudes of teachers and/or teacher candidates towards the value of justice (Chory-Assad, 2002;Balcı & Yanpar Yelken, 2010;Çengelci Köse, Gürdoğan Bayır, Köse & Yıldırım Polat, 2019;Memişoğlu & Taşkın, 2019;Yeşil, Zırhlıoğlu & Yayla, 2022). Consistent with results of other studies is, Namdar & Akbayrak (2019) investigation of the perceptions of gifted primary school 3rd grade students about the value of justice after the drama technique. However, very few studies have examined secondary school students' perceptions of the value of justice (Çakmak, 2016;Elbay, 2020;Üztemur, Dinç & İnel, 2018) and their metaphorical perceptions (İnel, Urhan & Ünal, 2018;Öner & Mindivanlı Akdoğan, 2021) aimed to reveal.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this context, many studies have been conducted to determine the perceptions and attitudes of teachers and/or teacher candidates towards the value of justice (Chory-Assad, 2002;Balcı & Yanpar Yelken, 2010;Çengelci Köse, Gürdoğan Bayır, Köse & Yıldırım Polat, 2019;Memişoğlu & Taşkın, 2019;Yeşil, Zırhlıoğlu & Yayla, 2022). Consistent with results of other studies is, Namdar & Akbayrak (2019) investigation of the perceptions of gifted primary school 3rd grade students about the value of justice after the drama technique. However, very few studies have examined secondary school students' perceptions of the value of justice (Çakmak, 2016;Elbay, 2020;Üztemur, Dinç & İnel, 2018) and their metaphorical perceptions (İnel, Urhan & Ünal, 2018;Öner & Mindivanlı Akdoğan, 2021) aimed to reveal.…”
Section: Introductionsupporting
confidence: 85%
“…It was also found that, although the word equality was perceived as a close concept to justice by the students, they did not treat them as equal. In parallel, in studies conducted by Elbay (2020), Mulhan (2007) and Namdar & Akbayrak (2019), students stated that justice has an important function in distinguishing between right and wrong. Similarly, in many studies conducted by secondary school 8th grade students, it was emphasized that the value of justice is different from equality, and that the value of equality is a prerequisite for ensuring justice; however, it was stated that providing equality alone would not be sufficient for justice (Dinç & Üztemur, 2016;Üztemur et al, 2018).…”
Section: Discussionmentioning
confidence: 99%